A narrative of cultural occupational performance/Uma narrativa de performance ocupacional cultural - Pollard, Nick (Cadernos Brasileiros de Terapia Ocupacional, 2016)
This article considers the occupational performance of cultural participation, specifically that of the author’s personal experience of being a “worker writer” and grassroots activist in the Federation of Worker Writers and Community Publishers (FWWCP). The FWWCP was a UK based organisation made up of co-operative publishers, history, literacy and writing workshops which produced narratives and other forms of writing about ordinary people’s experiences of everyday life in contemporary Britain. The author relates these experiences to occupational therapy’s concern with the meaning of occupation, and uses heuristic methods to reflect on the connections between this form of community activism through cultural activity and occupational concepts. The paper explores issues of the representation of social class and political consciousness which have not been visible in the professional discourse on occupation. It concludes that there is a strong case for the exploration of autobiographical and community writing in developing understanding of the cultural basis of occupation.